Performance and emissions of lemon peel oil biodiesel powered single cylinder direct injection diesel engine loaded with ceria nanoparticles additives and stabilized zirconia coating. (2022) - Udayakumar, M.; Sivaganesan, S.; Sivamani, S.
Abstract: The main aim of the present work is to examine the performance and emission characteristics of single cylinder direct ignition diesel engine powered with 3 proportions of lemon peel biodiesel (B10, B20 and B30) using ceria nanoparticles and yttria-ceria-stabilized zirconia as fuel additive and thermal barrier coating (TBC) materials, respectively, using pure diesel as base fuel. From the results of the engine performance and exhaust analysis, the volumetric efficiency and friction power increases whereas specific fuel consumption decreases for coated engine and observed insignificant deviation for CO and CO2 emissions between coated and uncoated engines. Hence lemon peel biodiesel could be employed in diesel engine with ceria nano particle additive and yttria-ceria-stabilized zirconia TBC.